FIGURE 32 in A small collection of rare and new chitons (Mollusca: Polyplacophora) from the Tasmanian Museum and Art Gallery ... - Sirenko, Boris (Zenodo, 2023)
FIGURE 32. Stenosemus simplicissimus, Southern Ocean, Heard Island, (TMAG, E 26178), BL 7.0 mm: A. Middle part of radula; B. Central and first lateral teeth of radula. ... : Published as part of Sirenko, Boris, 2023, A small collection of rare and new chitons (Mollusca: Polyplacophora) from the Tasmanian Museum and Art Gallery, pp. 359-392 in Zootaxa 5325 (3) on page 387, DOI: 10.11646/zootaxa.5325.3.3, http://zenodo.org/record/8247001 ...